Tracking Clinical Competency Growth: A Longitudinal Study of Medical Students in a Multidisciplinary Emergency Department Internship Program - Sung TC; Shih HI; Kawaguchi T; Chi CH; Hsu HC (Journal of Multidisciplinary Healthcare, 2025)
Tzu-Ching Sung,1 Hsin-I Shih,2– 4 Takeshi Kawaguchi,5 Chih-Hsien Chi,2,3 Hsiang-Chin Hsu3,6 1School of Medicine for International Students, College of Medicine, I-Shou University, Kaohsiung, Taiwan; 2Department of Emergency Medicine, National Cheng Kung University Hospital, National Cheng Kung University, Tainan, Taiwan; 3Department of Emergency Medicine, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 4Department of Public Health, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 5Department of Emergency and Critical Care Medicine, St. Marianna University School of Medicine, Kanagawa, Japan; 6School of Medicine, College of Medicine, National Cheng Kung University, Tainan, TaiwanCorrespondence: Hsiang-Chin Hsu, Department of Emergency Medicine, National Cheng Kung University Hospital, National Cheng Kung University, No. 138, Shengli Road, North Dist, Tainan City, 704302, Taiwan, Tel +886-6-235-3535 ext. 4381 ; +886-919-157-167, Email i3593120@gmail.comBackground: Emergency department (ED) internships are essential for developing core clinical competencies in medical students. This study evaluates the weekly progression of key competencies during a structured three-week ED internship and examines the impact of extending the program from two to three weeks. Additionally, it considers how such training supports students’ readiness for multidisciplinary, team-based healthcare environments.Methods: This retrospective longitudinal study analyzed a total of 2068 workplace-based assessment (WBA) forms collected from June 2018 to May 2020. Each WBA evaluated ten key clinical competencies: learning attitude, history taking, clinical judgment, medical knowledge, prescription, communication, patient education, literature appraisal, oral presentation, and documentation. A subgroup of 133 medical students who completed the full three-week internship with complete WBA records was included in the longitudinal analysis. Generalized Estimating Equations (GEE) modeling assessed performance trends and inter-cohort differences between 2018 and 2019.Results: Significant improvements were observed across all competencies, with the most notable gains in history taking, clinical judgment, communication, prescription, and documentation. Learning attitude scores increased from 4.46 (SD = 0.66) in Week 1 to 4.58 (SD = 0.58) in Week 3. Prescription and documentation improved from 3.85 and 4.17 to 4.06 and 4.32, respectively. GEE analysis confirmed significant performance gains by Week 3 (p = 0.0064). Students in 2019 outperformed those in 2018 (p = 0.0318), suggesting that curriculum refinements enhanced educational outcomes.Conclusion: A structured three-week ED internship significantly enhances medical students’ clinical competencies, particularly in areas fundamental to multidisciplinary care such as communication, clinical judgment, and documentation. The extended duration promotes deeper clinical immersion and fosters skill reinforcement through real-time feedback and collaborative practice. These findings underscore the importance of sustained, structured clinical experiences in preparing students to function effectively within interdisciplinary healthcare teams. Further research should investigate optimal training durations and integrative teaching strategies to support competency-based, team-oriented medical education.Keywords: clinical competency progression, emergency training, medical internships, diagnostic reasoning, multidisciplinary care, medical education